Pemberdayaan Masyarakat dengan Skrining CKG dan Pelatihan Akupresur untuk Hipertensi di Desa Gumulan - Sholichan Badri; Nurtama Aditya Nugraha (Health Care : Journal of Community Service, 2026)
A community service initiative addressing hypertension among adults and the elderly in Gumulan Village was conducted to enhance knowledge and provide acupressure training as a non-pharmacological intervention. Hypertension is a highly relevant public health issue for this initiative in Gumulan Village, Klaten, due to its high disease burden, frequent lack of awareness, and poor control—particularly among more vulnerable socioeconomic groups. The activities included health education, basic health screenings, and acupressure training for hypertension management. Results showed that 80 participants underwent health screenings; the findings revealed a mean systolic blood pressure of 137.26 ± 18.69 mmHg and a mean diastolic blood pressure of 83.00 ± 11.38 mmHg. Mean levels for total cholesterol, uric acid, and blood glucose were 215.85 ± 37.37 mg/dL, 5.98 ± 1.60 mg/dL, and 136.01 ± 51.51 mg/dL, respectively. This initiative increased residents' knowledge and provided safe complementary care. The program was deemed beneficial, and its continuation is recommended.